FACTORS RELATING TO UNMET NEEDS OF IRISH MS PATIENTS. (29th November 2012) - Lonergan, R; Kinsella, K; Fitzpatrick, P; Duggan, M; Jordan, S; Bradley, D; Hutchinson, M; Tubridy, N
Abstract : Background: Non-pharmacological MS-related needs may be overlooked during fund allocation.Identification of unmet needs (UN) and associated clinical/demographic factors may inform service planning and guide resource allocation to optimise care. Aim: To identify unmet MS-related needs and associated factors in Irish MS patients. Patients and Methods: Observational study in three regions: South Dublin (urban), Donegal and Wexford (rural). Patients completed a validated Needs Assessment Questionnaire (NAQ). Univariate and multivariate analyses were performed. Results: 325 patients completed NAQ: 52.3% reported UN relating to MS: 1 UN in 27%, ≥2 in 73%, ≥5 in 24%. Univariate analysis: UN related to EDSS >6.5 (p<0.001), progressive subtype (p<0.001), increased age (p=0.003), MS duration (p=0.003). By multivariate analysis: increasing EDSS and rural residence (p<0.05).UN included: physiotherapy 57.1%, social 43.5%, financial 33.5%, employment 29.4%, occupational therapy 28.8%, home adaptations 27.7%. Discussion: Over 50% reported UN, suggesting that non-pharmacological needs are suboptimally addressed, particularly in older, more disabled patients with progressive MS. Increasing EDSS and rural residence survived multivariate analysis, highlighting need for increased fund allocation, especially towards community support and multidisciplinary service development. Identifying unmet needs and associated factors may inform service planning and emphasizes need for improved resources.